Indonesia's Migrant Domestic Workers within ASEAN Community Framework: A Societal and Economic Security Approach - Anggia Utami Dewi; Adityo Darmawan Sudagung (Intermestic: Journal of International Studies, 2017)
This paper aims to analyze the issue of Indonesia's migrant domestic workers within the framework of ASEAN Community beyond 2015. With the government's plan to stop the sending of Indonesia's migrant domestic worker abroad in 2017, one of possible direct effects would be the rise of unemployment rate. On other hand, one of the consequences of the integrated ASEAN Economic Community is the free movement of people, commodities and services between ASEAN member countries. Higher level of people's flow will increase connectivity as well competition. Using a qualitative approach of method, this paper elaborates the discourse of the Indonesia's migrant domestic workers, using the societal and economic security perspective as analytical framework.